2014 IEEE Global Conference on Signal and Information Processing (GlobalSIP) 2014
DOI: 10.1109/globalsip.2014.7032284
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic range expansion of video sequences: A subjective quality assessment study

Abstract: The goal of this paper is to assess whether existing solutions to expand low dynamic range (LDR) still images to high dynamic range (HDR) displays can apply to moving pictures. To this end, we conduct a subjective quality assessment test on four state-of-the-art expansion operators, using high-quality input LDR content. Our results show that, perhaps surprisingly, no temporal artifacts, such as flickering due to global illumination changes, are introduced applying frame-based algorithms. In addition, they conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
(39 reference statements)
1
11
0
Order By: Relevance
“…However, dynamic range expansion can be traced back to a simple trick presented by Landis [143], for the purpose of using LDR images in IBL. For display of LDR images on HDR displays, a number of perceptual studies have pointed to the fact that a global mapping may be preferred, either using a gamma function [36,177,178] or a linear scaling [8,226].…”
Section: Single-exposure Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, dynamic range expansion can be traced back to a simple trick presented by Landis [143], for the purpose of using LDR images in IBL. For display of LDR images on HDR displays, a number of perceptual studies have pointed to the fact that a global mapping may be preferred, either using a gamma function [36,177,178] or a linear scaling [8,226].…”
Section: Single-exposure Techniquesmentioning
confidence: 99%
“…Instead, they attempt at achieving the best visual performance in end applications such as HDR display or IBL. For display on an HDR capable device this means that global mappings are generally preferred [177,226], due to problems in reconstructing colors and details in over-exposed areas. Thus, saturated image regions remain saturated on the HDR display.…”
Section: Relation To Inverse Tone-mappingmentioning
confidence: 99%
“…The aim of these rTMOs is to increase the brightness and contrast of conventional (SDR) content in order to display it on modern HDR displays. Several studies exist that evaluate the performance of existing rTMOs including [4], [5], [14]. The study conducted by Abebe et al in [15], additionally explored the issue of colour reproduction when expanding the dynamic range of SDR images, but found that luminance reproduction is much more important.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing the perceived dynamic range of HDR content remains an unexplored phenomenon. This has a number of potential applications and fallouts in different fields: it can be used to optimize and evaluate inverse tone mapping operators [3], [4], [5], HDR compression methods and HDR reproduction systems [6]; it is an important attribute in the formation of aesthetic judgments [7]; it provides objective means to select source contents in HDR subjective studies [8]; and in general it would help to advance the understanding of lightness perception, by extending studies on the anchoring problem [2] to complex stimuli and HDR conditions.…”
Section: Introductionmentioning
confidence: 99%